Characterization of EBT3 radiochromic film for precise measurement of output factors in stereotactic radiosurgery - Alam, Nur Zarifha Zainol (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2015)
Radiochromic film become a demanding tool in a work of characterizing dosimetric properties in small field stereotactic radiosurgery. The aim of this project is to perform a comparative study in measuring output factor using EBT3 radiochromic film and PTW PinPoint Ion Chamber. Output factor measurements using EBT3 films and PTW PinPoint Ion Chamber were performed using 6MV photon beam from medical linear accelerator .The measurements was done in solid water phantom and CNMC Model 74-320 water phantom. Measurements were done at dmax (1.5cm ) depth inside water phantom and 100 cm source surface distance. Results: Percentage difference of measured output factor with EBT3 Gafchromic film and PTW Ion PinPoint Chamber was approximately 10-11%. Analysis on dose response for EBT3 and EBT2 gives difference approximately 4% in magnitude. The result obtained for scanning orientation study show minimal difference in output factors for different side orientation which differs by less than 2%. Variations for all doses were found to be less than 0.16 (net difference of optical density) for 4°C and 28°C but 0.026 for 37°C. Net optical density for the films stored in 37°C recorded huge difference in relative standard deviation which approximately only 4% compared to 4°C and 28°C which are 34-37% but still represents linear relationship with dose. EBT3 is suitable for measurements of output factor in stereotactic radiosurgery and can be use on validation of dose when high spatial resolution is required for clinical practice.